2015
DOI: 10.2500/aap.2015.36.3909
|View full text |Cite
|
Sign up to set email alerts
|

Omalizumab in the treatment of allergic bronchopulmonary aspergillosis: One center's experience with 14 cases

Abstract: Omalizumab provided a clinically important reduction in exacerbations and steroid requirement, and improved asthma symptoms and pulmonary function parameters in patients with asthma and ABPA who had previously shown an unsatisfactory response to Global Initiative for Asthma step 4 treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 0 publications
2
49
1
Order By: Relevance
“…Collins et al observed a significant improvement in ACT symptom scores in patients with ABPA after omalizumab treatment (30). Aydın et al reported that compared to the basal score, mean ACT score had increased after starting omalizumab treatment (21). Similar to these two reports, omalizumab treatment improved asthma symptoms and significantly increased the mean ACT score in both the first and third years in our study.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Collins et al observed a significant improvement in ACT symptom scores in patients with ABPA after omalizumab treatment (30). Aydın et al reported that compared to the basal score, mean ACT score had increased after starting omalizumab treatment (21). Similar to these two reports, omalizumab treatment improved asthma symptoms and significantly increased the mean ACT score in both the first and third years in our study.…”
Section: Discussionsupporting
confidence: 87%
“…Patients who do not respond to corticosteroids antifungal medication can be used (29). Recently, reports have described effective results with the administration of omalizumab in patients with severe allergic asthma and ABPA (21,29). In our study 5 (33.3%) patients with severe asthma had unsatisfactory response to anti-asthmatic agents.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…They indicate that the serum EDN level may be a useful marker for monitoring persistent airflow limitation in adult patients with allergic asthma who are positive for house-dust-specific IgE antibodies. Also within this issue, Aydın et al 3 report on the potential utility of total serum IgE as a biomarker for responsiveness to omalizumab in patients with allergic bronchopulmonary aspergillosis.…”
mentioning
confidence: 99%